Potential to recover a record of Holocene climate and sea ice from Müller Ice Cap, Canada - David Armond Lilien; Niels Fabrin Nymand; Tamara Annina Gerber; Daniel Steinhage; Daniela Jansen; Laura Thomson; Madeline Myers; Steven Franke; Drew Taylor; Prasad Gogineni; Marcos Lemes; Bo Møllesøe Vinther; et al. (Journal of Glaciology)
Müller Ice Cap sits on Umingmat Nunaat (Axel Heiberg Island), Nunavut, Canada, ~ 80°N. Its high latitude and elevation suggest it experiences relatively little melt and preserves an undisturbed paleoclimate record. Here, we present a suite of field measurements, complemented by remote sensing, that constrain the ice thickness, accumulation rate, temperature, ice-flow velocity, and surface-elevation change of Müller Ice Cap. These measurements show that some areas near the top of the ice cap are more than 600 m thick, have nearly stable surface elevation, and flow slowly, making them good candidates for an ice core. The current mean annual surface temperature is −19.6 °C, which combined with modeling of the temperature profile indicates that the ice is frozen to the bed. Modeling of the depth-age scale indicates that Pleistocene ice is likely to exist with measurable resolution (300–1000 yr m−1) 20–90 m from the bed, assuming that Müller Ice Cap survived the Holocene Climatic Optimum with substantial ice thickness (~400 m or more). These conditions suggest that an undisturbed Holocene climate record could likely be recovered from Müller Ice Cap. We suggest 91.795°W, 79.874°N as the most promising drill site.